Seroprevalence and Public Health Significance of Toxoplasmosis in Small Ruminants of Pastoral Community in Yabello District, Borana Zone, Southern Ethiopia - Kula Jilo; Dechassa Tegegne; Sadik Kasim; Golo Dabasa; Wubishet Zewdei (Veterinary Medicine International)
Toxoplasmosis is a zoonotic protozoan disease. Data on seroepidemiology of toxoplasmosis in Ethiopia is scarce, almost null in the pastoral area of the Borana zone. The study was carried out to determine the seroprevalence, to identify risk factors of toxoplasmosis in sheep and goats, and to assess the awareness level of pastoralists about toxoplasmosis in the Yabello district of Borana zone, Southern Ethiopia. A cross-sectional study was conducted from November 2016 to April 2017 in six peasant associations of the Yabello district of Borana zone, Southern Ethiopia. A total of 400 serum samples of randomly selected small ruminants owned by pastoralists were examined to detect antibodies specific to Toxoplasma gondii using Latex Agglutination Test (SPINREACT, Girona, Spain). A semistructured questionnaire survey was used to conduct a face-to-face interview with owners (n = 100) of sampled flocks. Logistic regression analysis was used to determine the association of hypothesized risk factors. The overall seroprevalence was 52.8% of which 57.8 and 47.8% were sheep and goats, respectively. Univariate logistic regression analysis revealed a higher seroprevalence ratio of T. gondii infection in sheep than goats (COR: 1.95, 95% CI: 1.226–3.112; P = 0.005). Multivariate logistic regression analysis indicated significantly higher odds of acquiring T. gondii infection in adult animals (sheep: (AOR = 2.26, 95% CI: 1.323–3.874; P = 0.003), goats: (AOR = 2.15; 95% CI: 1.009–4.579; P = 0.047)), female sheep (AOR = 2.45; CI: 1.313–4.568; P = 0.005), animals from lowland areas (sheep: (AOR = 2.28; CI: 1.190–4.356; P = 0.013), goat: (AOR = 3.27; CI: 1.386–7.723; P = 0.007)), animal drinking lake water (sheep: (AOR = 1.93; CI: 1.011–3.698; P = 0.046), goat: (AOR = 2.96; CI: 1.297–6.771; P = 0.010)), and goats with history of abortion (AOR = 2.42; CI: 1.242–4.711; P = 0.009) than young animals, male (sheep), animals from midland areas, animals drinking wells water, and flock with no history of abortion (goat), respectively. Among respondents, 97.0% had no knowledge about toxoplasmosis and 75.0% drink raw milk and consume the meat of sheep and goats. 80.0% of respondents had no knowledge about the risk of cats to human and animal health while 70.0% of them had domestic cats and practice improper fetal body handling. Highly prevailing toxoplasmosis in small ruminants of the Yabello district might pose a serious economic loss and be a potential public health threat to the extremely vulnerable pastoralists. Therefore, awareness and further studies are warranted to tackle the economic and public health consequences of T. gondii infection.